Alumni perceptions of registered psychological counsellor training at a South African university - Joubert, C.; Hay, J. (South African Journal of Higher Education, 2021)
In this article the strengths, caveats and suggestions for improvement of a BEd Hons programme in Educational Psychology presented at a traditional South African university from the viewpoint of 10 alumni students who were part of the 2016 cohort, are explored. The programme under investigation has been running since 2003 and is aimed at training mid-level psychological counsellors who have to pass the Health Professions Council of South Africa’s (HPCSA) board examination for Psychology to formally qualify as registered counsellors. The HPCSA instituted the category of registered counsellor early in the 2000s to provide a route to basic psychological support for the majority of citizens without access to registered psychologists. In order to achieve the aim of this research, qualitative individual telephone interviews were conducted in 2017 to gather data from the counsellor alumni of the 2016 cohort. In total, 10 of a possible 26 participants voluntarily participated in the study. The perceptions of the participants were analysed, and findings suggest that the BEd Hons programme has the following strengths: weekly supervision by experienced lecturers enabled knowledge obtained through theoretical coursework to be applied during the practicum; various professional skills were also gained during the practicum, enabling students to feel competent in the workplace. A very strong focus on clients from disadvantaged communities was also seen as a particular strength. Some caveats were inadequate information about the psychological and job-related implications of the programme. Suggestions indicated that the organisation of the theoretical and practicum components could be reconsidered so as to optimise the programme in future. Furthermore, it was found that transformation in this type of higher education programme is needed on a theoretical and practical level by ensuring broadened access to the programme and listening to the voices of the students regarding the curriculum.